Efficacy and Safety of Daprodustat Vs rhEPO for Anemia in Patients With Chronic Kidney Disease: A Meta-Analysis and Trial Sequential Analysis - Fu, Zhangning; Geng, Xiaodong; Chi, Kun; Song, Chengcheng; Wu, Di; Liu, Chao; Hong, Quan (Frontiers in Pharmacology, 2022)
Introduction: Daprodustat, a novel hypoxia-inducible factor prolyl-hydroxylase inhibitor (HIF-PHI), its efficacy and safety remain unclear. Thus, we conducted this meta-analysis aiming at investigating its efficacy and safety on the treatment of patients with chronic kidney disease (CKD)-related anemia. Methods: We systematically searched for relevant studies in PubMed, Embase, Cochrane Library and Clinical Trial Registries databases from inception until May 2021. We selected randomized controlled trials comparing daprodustat with recombinant human erythropoietin (rhEPO) in anemia patients with CKD with or without dialysis. Results: Five studies including 1097 patients met the inclusion criteria. For both nondialysis-dependent (NDD-) CKD and dialysis-dependent (DD-) CKD patients, the pooled results showed that there was no significant difference in the changes in hemoglobin levels between the daprodustat and rhEPO groups (mean difference (MD) = -0.04, 95% confidence interval (CI) = -0.76 to 0.68, P = 0.91; MD = 0.13, 95% CI = -0.75 to 1.01, P = 0.77; respectively). Iron metabolism parameters were optimized by daprodustat, for the observation of a significant increase in total iron binding capacity (TIBC), serum iron, and transferrin saturation (TSAT) (P＜0.05) in daprodustat groups compared with rhEPO groups in DD-CKD patients. In addition, the overall frequency of adverse events was similar between the daprodustat and rhEPO groups in both NDD-CKD and DD-CKD patients (relative risk (RR) = 1.03, 95%CI = 0.96, 1.10, P = 0.39; RR = 0.95, 95%CI = 0.90, 1.00, P = 0.07 respectively), and the trial sequential analysis (TSA) confirmed this result. The incidence of serious adverse events in the daprodustat group in DD-CKD patients was significantly lower than that of rhEPO group, but the TSA could not confirm this result. Conclusion: Daprodustat was noninferior to rhEPO in correcting anemia in both NDD-CKD and DD-CKD patients. However, daprodustat may be much safer for DD-CKD patients and can optimize iron metabolism. Daprodustat may be a promising alternative for the treatment of anemia in patients with CKD.